Malaria Community Health Workers in Eliminating Malaria in Banyumas Regency - Rejeki, Dwi Sarwani Sri; Nurlaela, Sri; Octaviana, Devi; Kusnanto, Hari; Murhandarwati, Elsa Herdiana (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2016)
Banyumas has not reached the elimination of malaria yet. One of the efforts is done by community empowerment by establishing malaria Community Health Workers (CHWs/JMD). JMD are people who conduct the discovery and medication of malaria in Active Case Detection (ACD). The research aims at describing JMDs attitude and knowledge towards the malaria elimination in Banyumas Regency in 2015. Quantitative research with cross sectional design was performed in the study. There were 15 JMDs spreading across in 7 public health centers/Puskesmas. The results show that most of JMDs were male with primary education background. They are mostly employed and do not join any training within 3 years. The average age of JMDs is 48.4 years old although there are some workers who are over 65 years old. 33.3% of JMDs are in low-medium categories, and there are 26.7% JMDs who have negative attitude to malaria. All JMDs have less skill such as not to do home visits as scheduled, not to do periodic reports, not to send blood preparations immediately and unstandardized of the blood preparation.